(untitled) (Advances in Applied Biological Research, 2025)
Traditional dietary patterns, developed over centuries, offer balanced nutrient profiles, cultural sustainability, and health benefits that are increasingly relevant in addressing modern diet-related chronic diseases. With rising rates of non communicable diseases (NCDs) such as cardiovascular disease, type 2 diabetes and obesity, global interest in diets like the Mediterranean, Indian traditional, Japanese and Nordic patterns has surged. These diets are rich in whole grains, fresh vegetables, fruits, legumes, nuts, healthy fats and fermented foods and low in processed sugars and trans fats. This review synthesizes recent literature (2018–2025) on the nutrient composition, health outcomes and potential integration strategies of traditional diets in contemporary health systems. Also explore the challenges of preserving cultural dietary practices in an era dominated by fast food and ultra-processed products. Data indicate that adopting traditional diets can reduce cardiovascular risk by up to 30%, improve glycaemic control, and support gut microbiota diversity, leading to improved overall well-being. The review concludes with recommendations for policymakers, healthcare providers, and individuals to adapt and sustain these dietary patterns in the modern context.